The preparation process of nitrogenous ferrovanadium with bottom-blowing nitriding in electrical arc furnace. (16th March 2017) - Liu, F.; Zhu, R.; Dong, K.; Bai, R.
Abstract : The flow field characteristics and stirring abilities of five kinds of bottom-blowing arrangements on the molten bath were researched in a 3t electrical arc furnace (EAF) with regular shape. The mixing time was measured by water experiment under different flow rates. Flow field characteristics of three-phase flow were simulated by numerical simulation. The average mixing time decreased with the flow rate and the radius of circle coincide increasing for the EAF with regular shape. Moreover, weakening counteracting force of counter-swirls could efficiently reduce mixing time than weakening impeding forces of sidewall with concentric circle arrangements at the tested conditions. Compared with 6R bottom-blowing arrangement at industrial application research, the 7R bottom-blowing arrangement, which was determined by the water model experiments and the simulations, could stir molten better in nitriding process, which agreed well with the experimental results of the water experiment and the numerical simulation.